2014
DOI: 10.1002/qua.24668
|View full text |Cite
|
Sign up to set email alerts
|

Hohenberg–Kohn theorems in the presence of magnetic field

Abstract: In this article, we examine Hohenberg–Kohn theorems for Current Density Functional Theory, that is, generalizations of the classical Hohenberg–Kohn theorem that includes both electric and magnetic fields. In the Vignale and Rasolt formulation (Vignale and Rasolt, Phys. Rev. Lett. 1987, 59, 2360), which uses the paramagnetic current density, we address the issue of degenerate ground states and prove that the ensemble‐representable particle and paramagnetic current density determine the degenerate ground states.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 17 publications
0
71
0
Order By: Relevance
“…For N = 1, a Hohenberg-Kohn theorem exists formulated with the total current density [5,6], i.e., ρ(r) and j(r) determine V (r) and A(r) up to a gauge transformation. In particular, A(r) = a(ρ, j; r) − ∇χ(r) for some function χ(r).…”
Section: Non-existence Of a Variational Principle Forẽ Vamentioning
confidence: 99%
See 3 more Smart Citations
“…For N = 1, a Hohenberg-Kohn theorem exists formulated with the total current density [5,6], i.e., ρ(r) and j(r) determine V (r) and A(r) up to a gauge transformation. In particular, A(r) = a(ρ, j; r) − ∇χ(r) for some function χ(r).…”
Section: Non-existence Of a Variational Principle Forẽ Vamentioning
confidence: 99%
“…Since the proofs in [3] and [4] have been shown to contain errors (cf. [5,6]), the existence of such a theorem remains an open question except for the one-electron case. For a system with only one electron, however, it can be shown that the particle density and the total current density determine the potentials up to a gauge transformation [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most conservative extensions to date are the magnetic-field density-functional theory (BDFT) due to Grayce and Harris [5] as well as the paramagnetic current density functional theory (CDFT) due to Vignale and Rasolt [6]. Less clear-cut are the attempts to formulate current density functional theories based on the physical current density due to Diener [7] as well as Pan and Sahni [8], which both suffer from gaps or mistakes in the proposed proofs of central results [9][10][11][12][13][14]. Another possible route to incorporate external magnetic fields is via a relativistic density-functional theory based on the Dirac equation, which is likely to involve the physical current density as a basic variable.…”
Section: Introductionmentioning
confidence: 99%